Preparation and application of polyclonal antibody against a cysteine-rich protein encoded by Chinese wheat mosaic virus - DAI Yuanxing; GUO Liuming; HE Jing; SHEN Zhengrong; GENG Yanfei; LÜ Mingfang; YUAN Zhengjie; LI Jing; ZHANG Hengmu (浙江大学学报. 农业与生命科学版, 2023)
Chinese wheat mosaic virus (CWMV) is one of the most important pathogens causing mosaic disease in wheat and has threatened the yield and quality of wheat for a long time. Cysteine-rich protein (CRP) of CWMV plays important and complex roles in viral infection. To further study CRP functions and CWMV infection mechanisms, the CRP coding region was amplified by reverse transcription-polymerase chain reaction (RT-PCR) from leaves of CWMV-infected wheat and cloned into the prokaryotic expression vector pET-32a. The recombinant plasmid pET-CRP was transformed into Escherichia coli BL21 (DE3) for inducible expression. The recombinant CRP was purified by nickel-column affinity chromatography and used as an antigen to immunize New Zealand white rabbits for polyclonal antibody preparation. A series of immunological assays, including Western blot, indirect enzyme-linked immunosorbent assay (ELISA) and dot ELISA, showed that the purified CRP antibody had high specificity, and its titer was as high as 1∶4 096 000, which was four times higher than that of the unpurified antibody. The antibody could recognize 0.5 ng antigen, showing its high sensitivity. In addition, the purified CRP antibody could specifically and sensitively recognize native CRP even at a 1∶120 000 dilution. In conclusion, the polyclonal antibody can be not only used for precise diagnosis of the CWMV-infected plant samples from fields, but also applied to detect CRP expressed transiently in plants, which lays a foundation for subsequent detection, quantification and subcellular localization of CRP.